Characterizing Toxicity on Facebook Comments in Brazil - Guimarães, Samuel S.; Reis, Julio C. S.; Ribeiro, Filipe N.; Benevenuto, Fabrício (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2020: Proceedings of the 26th Brazilian Symposium on Multimedia and the Web, 2020)
On social media platforms, comments associated with news pieces are usually filled with negativity and toxicity, many times promoting flamed discussions and insults among users. Although designed to encourage conversations and interactions, the high toxicity might end up contributing to create a hostile environment in the online space, which is detrimental to both social media platforms and their users. In this work, we provide a large-scale diagnostic about the toxicity in comments associated with news shared on Facebook. To do that, we collected all posts and comments from relevant pages during a major political event in Brazil, the release of Former President Lula from prison. We then used the Perspective API from Google to measure the toxicity of the comments and posts. Our analysis of the toxicity unveils features that influence toxicity associated with the news, especially in relation to public figures. We hope our findings may affect the design of better content policies able to mitigate the problem.